A polyolefin PP diaphragm with improved crystal point problem and preparation method thereof
During the preparation process of polyolefin PP separators, using specific formulas of PP particle masterbatch, main antioxidant and auxiliary antioxidant, combined with high-temperature melt extrusion, casting, stretching and other processes, the problem of poor crystal points in the separator is solved, and the safety and circulation performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411788810.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-01
AI Technical Summary
There are crystal points on the membrane surface in the polyolefin PP separator, which causes the crystal points to puncture the separator during the shaping process or form a weak area of the separator, resulting in poor short circuit of the battery cell and lithium extraction, affecting the safety and circulation performance of the battery.
Using a formula including PP particle masterbatch, main antioxidant and auxiliary antioxidant, high-temperature melt-extrusion is performed in an extruder after stirring and mixing through a feeding kettle, followed by casting of T-shaped dies and cooling and forming, followed by composite and longitudinal stretching, and finally, a polyolefin PP diaphragm that improves crystal point problems is prepared by a layering machine and a slitting equipment.
It effectively reduces the problem of poor crystal points in the diaphragm, reduces the problems of breakage, low thickness, and small breathability caused by crystal points, improves the safety and circulation performance of the battery, and reduces the occurrence of poor cell short circuit and lithium separation phenomena.
Smart Images

Figure CN119735892A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, in particular to a polyolefin PP diaphragm with improved crystal point problem and a preparation method thereof. Background Art
[0002] The performance of the diaphragm determines the interface structure and internal resistance of the battery, and directly affects the battery's capacity, cycle, safety performance and other characteristics. A diaphragm with excellent performance plays an important role in improving the overall performance of the battery. The main function of the diaphragm is to separate the positive and negative electrodes of the battery to prevent the two electrodes from contacting and short-circuiting. In addition, it also has the function of allowing electrolyte ions to pass through. The diaphragm material is non-conductive, and its physical and chemical properties have a great influence on the performance of the battery. Different types of batteries use different diaphragms. For lithium battery series, since the electrolyte is an organic solvent system, a diaphragm material that is resistant to organic solvents is required. Generally, a high-strength thin-film polyolefin porous membrane is used. At this stage, the market is mainly dry diaphragms and wet diaphragms;
[0003] Film crystal point is one of the biggest difficulties in the processing of plastic film. How to effectively eliminate, reduce and control the crystal point problem is the biggest challenge for film engineers, especially the processing of multi-layer co-extrusion technology films. Because the causes of crystal points are complex, in the process of co-extrusion film processing, different materials and resins with different processing characteristics must be molded in the same die head and under the same processing conditions, and the elimination of crystal points is more difficult. Crystal points are actually transition polymers, which belong to high-molecular materials with polymers at the crystal point position. The molecular weight of the polymer is higher than the molecular weight of the surrounding polymers of the same type. Because the polymer at the crystal point has a higher melting point, when it melts, the melt has a higher viscosity. The crystal point position is suitable for casting or blow molding. It cannot be evenly dispersed and mixed with the surrounding polymers of the same type. After melt casting or blow molding, it solidifies before the surrounding polymers of the same type. Because the solidified body of the transition polymer in the form of long strips or spherical shapes is called crystal point in the diaphragm production industry.
[0004] Polyolefin separators have crystal points on the membrane surface. Crystal points can easily cause the cell to pierce the separator or form weak areas in the separator during the shaping process. This may lead to short circuits in the cell safety test and lithium deposition during the cell recycling process. This makes the battery safety very critical. Therefore, it has become a trend to improve the crystal points of polyolefin separators. Summary of the invention
[0005] In view of the deficiencies of the above-mentioned prior art, the present invention provides a polyolefin PP diaphragm with improved crystal point problem and a preparation method thereof, which can reduce the poor crystal point during the diaphragm manufacturing process, reduce the problems of PP diaphragm cracks, low thickness, low air permeability, etc. caused by crystal points, and can solve the problem of crystal points piercing the diaphragm or forming weak areas of the diaphragm during the preparation of the battery cell, reduce the problem of battery cell short circuit defects in battery cell safety testing, and reduce the problem of lithium plating during battery cell recycling.
[0006] The technical solution provided by the present invention is a polyolefin PP diaphragm with improved crystal point problem, characterized in that it comprises the following components in parts by weight: 97-99 parts of PP particle masterbatch, 0.1-2 parts of main antioxidant, and 0.1-2 parts of auxiliary antioxidant.
[0007] Furthermore, 98.5 parts of PP particle masterbatch, 0.75 parts of primary antioxidant, and 0.75 parts of auxiliary antioxidant.
[0008] Furthermore, the main antioxidant is a highly heat-resistant hindered lipid or phenolic antioxidant, including but not limited to 1010, 1098, etc. The main antioxidant plays a long-term and continuous antioxidant role by capturing free radicals generated during the degradation of plastics.
[0009] Furthermore, the auxiliary antioxidant is a phosphate ester, fat-soluble antioxidant, including but not limited to 168, 626, etc. The antioxidant purpose is achieved by decomposing the peroxide produced by further degradation of the plastic, mainly providing thermal processing stability.
[0010] Furthermore, the molecular weight of the PP particle masterbatch is 100,000-600,000.
[0011] Another technical solution provided by the present invention is a method for preparing a polyolefin PP diaphragm with improved crystal point problem, comprising the following steps:
[0012] S1: Add the raw materials into the feeding kettle according to the following mass parts: 97-99 parts of PP particle masterbatch, 0.1-2 parts of primary antioxidant, and 0.1-2 parts of auxiliary antioxidant;
[0013] S2: The feeding kettle stirs and mixes the added materials, and automatically feeds the materials to the extruder through a precise metering scale, and then melts and extrude them at high temperature in the extruder;
[0014] S3: The high-temperature molten fluid is cast through a T-die and cooled by a casting roller;
[0015] S4: Roll up the cast film and combine the four rolls of cast film into a large roll;
[0016] S5: The cast film after the composite large roll is longitudinally stretched by a stretching machine, wherein the stretching equipment includes online heat treatment, heating stretching, heat setting, and winding;
[0017] S6: The stretched and rolled film is peeled off with different layers by a layering machine and rolled into a semi-finished film;
[0018] S7: The semi-finished film is passed through a slitting device and cut into a required width according to requirements to obtain a finished film.
[0019] Furthermore, in step S1, the mass ratio of the primary antioxidant to the auxiliary antioxidant is 1:1.
[0020] Furthermore, in step S1, the feeding kettle unloading weighing scale is ≥50kg / h, the accuracy is ≤±0.5%, the feeding kettle stirring speed is 100-300rmp / s, and the stirring time is 2-4min.
[0021] Furthermore, in the step S2, the screw of the extruder is a single screw or a twin screw, the melt temperature of the extruder is 200-260°C, the film thickness is cooled to ≥100um in the step S3, and the casting roller temperature is 10-40°C.
[0022] Furthermore, in step S5, the longitudinal stretching ratio is controlled to be 6-12 times, the longitudinal stretching speed is 5-20m / min, and in step S7, the slitting machine speed is controlled to be 80-200m / min, the unwinding tension is 20-50N, the winding tension is 5-20N, and the winding taper is gradually reduced at a ratio of 8%-20%.
[0023] The beneficial effects of the present invention are:
[0024] 1. The present invention adds a primary antioxidant for capturing peroxide free radicals and an auxiliary antioxidant for decomposing hydroperoxides into the feeding kettle, which mainly provides thermal processing stability, is beneficial to the processing fluidity of polyolefin PP materials, reduces the melt viscosity, and allows polymers of different molecular weights to be evenly dispersed.
[0025] 2. The present invention uniformly mixes the PP masterbatch, the main antioxidant and the auxiliary antioxidant, and forms a film by melt extrusion and stretching. The different melting points and compatibility of the antioxidants are utilized to eliminate the phenomenon that the polymer solution sticking to the surface of the screw is heated for too long, and the continuous polymerization of the polymer by the residual catalyst is prevented. Finally, the polymers can be fully and evenly fused in the melting process of the extruder, and the crystal points formed as the dissolved crystal points due to the uneven heating of polymers with different molecules are reduced, so as to prevent the battery from having a hipot failure in a short circuit test, and lithium ions cannot pass through the crystal point area during the charge and discharge process of the battery cell, resulting in lithium precipitation in the battery for a long time. The safety of the battery is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION
[0027] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with embodiments. The embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.
[0028] Embodiment 1
[0029] A polyolefin PP diaphragm with improved crystal point problem, comprising a polyolefin PP masterbatch, a main antioxidant of pentaerythritol ester, model number of antioxidant 1010, and an auxiliary antioxidant of butylated alkyltoluene, model number of 168. Specifically comprising the following components by mass: 98.9 parts of PP particle masterbatch, 0.4 parts of main antioxidant, and 0.7 parts of auxiliary antioxidant.
[0030] The specific preparation method is as follows: comprising the following steps:
[0031] S1: Add PP particle masterbatch, primary antioxidant and auxiliary antioxidant into the feeding kettle;
[0032] S2: The feeding kettle stirs and mixes the added materials, and automatically feeds the materials to the extruder through a precise metering scale, and then melts and extrude them at high temperature in the extruder;
[0033] S3: The high-temperature molten fluid is cast through a T-die and cooled by a casting roller;
[0034] S4: Roll up the cast film and combine the four rolls of cast film into a large roll;
[0035] S5: The cast film after the composite large roll is longitudinally stretched by a stretching machine, wherein the stretching equipment includes online heat treatment, heating stretching, heat setting, and winding;
[0036] S6: The stretched and rolled film is peeled off with different layers by a layering machine and rolled into a semi-finished film;
[0037] S7: The semi-finished film is passed through a slitting device and cut into a required width according to requirements to obtain a finished film.
[0038] In step S1, the feeding kettle is weighed at 80 kg / h with an accuracy of ≤±0.5%, the stirring speed of the feeding kettle is 200 rmp / s, and the stirring time is 3 min.
[0039] In the step S2, the screw of the extruder is a single screw, the melt temperature of the extruder is 245°C, and in the step S3, the film thickness is cooled to 125um, and the temperature of the casting roller is 35°C.
[0040] In step S5, the longitudinal stretching ratio is controlled to be 10.2 times, the longitudinal stretching speed is 15 m / min, and in step S7, the slitting machine speed is controlled to be 150 m / min, the unwinding tension is 35 N, the winding tension is 13 N, and the winding taper is gradually reduced at a rate of 15%.
[0041] Embodiment 2
[0042] A polyolefin PP diaphragm with improved crystal point problem, comprising a polyolefin PP masterbatch, a main antioxidant of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine, model 1098; and an auxiliary antioxidant of butylated alkyltoluene, model 168. Specifically comprising the following components in parts by mass: 98 parts of PP particle masterbatch, 0.9 parts of the main antioxidant, and 1.1 parts of the auxiliary antioxidant.
[0043] The specific preparation method is as follows: comprising the following steps:
[0044] S1: Add PP particle masterbatch, primary antioxidant and auxiliary antioxidant into the feeding kettle;
[0045] S2: The feeding kettle stirs and mixes the added materials, and automatically feeds the materials to the extruder through a precise metering scale, and then melts and extrude them at high temperature in the extruder;
[0046] S3: The high-temperature molten fluid is cast through a T-die and cooled by a casting roller;
[0047] S4: Roll up the cast film and combine the four rolls of cast film into a large roll;
[0048] S5: The cast film after the composite large roll is longitudinally stretched by a stretching machine, wherein the stretching equipment includes online heat treatment, heating stretching, heat setting, and winding;
[0049] S6: The stretched and rolled film is peeled off with different layers by a layering machine and rolled into a semi-finished film;
[0050] S7: The semi-finished film is passed through a slitting device and cut into a required width according to requirements to obtain a finished film.
[0051] In the step S1, the feeding kettle is weighed at 75 kg / h with an accuracy of ≤±0.5%, the stirring speed of the feeding kettle is 190 rmp / s, and the stirring time is 3.2 min.
[0052] In the step S2, the screw of the extruder is a single screw, the melt temperature of the extruder is 237°C, the film thickness is 126um and the casting roller temperature is 31°C in the step S3.
[0053] In step S5, the longitudinal stretching ratio is controlled to be 10.3 times, the longitudinal stretching speed is 12.4 m / min, and in step S7, the slitting machine speed is controlled to be 145 m / min, the unwinding tension is 38 N, the winding tension is 11 N, and the winding taper is gradually reduced at a rate of 12%.
[0054] Embodiment 3
[0055] A polyolefin PP diaphragm with improved crystal point problem, comprising a polyolefin PP masterbatch, a primary antioxidant of pentaerythritol ester, model 1010, and a secondary antioxidant of bis(2.4-di-tert-butylphenyl)pentaerythritol diphosphite, model 626. Specifically comprising the following components by mass: 98.5 parts of PP particle masterbatch, 0.75 parts of primary antioxidant, and 0.75 parts of secondary antioxidant.
[0056] The specific preparation method is as follows: comprising the following steps:
[0057] S1: Add PP particle masterbatch, primary antioxidant and auxiliary antioxidant into the feeding kettle;
[0058] S2: The feeding kettle stirs and mixes the added materials, and automatically feeds the materials to the extruder through a precise metering scale, and then melts and extrude them at high temperature in the extruder;
[0059] S3: The high-temperature molten fluid is cast through a T-die and cooled by a casting roller;
[0060] S4: Roll up the cast film and combine the four rolls of cast film into a large roll;
[0061] S5: The cast film after the composite large roll is longitudinally stretched by a stretching machine, wherein the stretching equipment includes online heat treatment, heating stretching, heat setting, and winding;
[0062] S6: The stretched and rolled film is peeled off with different layers by a layering machine and rolled into a semi-finished film;
[0063] S7: The semi-finished film is passed through a slitting device and cut into a required width according to requirements to obtain a finished film.
[0064] In the step S1, the feeding kettle is weighed at 85 kg / h with an accuracy of ≤±0.5%, the stirring speed of the feeding kettle is 265 rmp / s, and the stirring time is 3.6 min.
[0065] In the step S2, the screw of the extruder is a single screw, the melt temperature of the extruder is 249°C, the film thickness is 132 um and the casting roller temperature is 36°C in the step S3.
[0066] In step S5, the longitudinal stretching ratio is controlled to be 11 times, the longitudinal stretching speed is 13.6 m / min, and in step S7, the slitting machine speed is controlled to be 137 m / min, the unwinding tension is 39 N, the winding tension is 14 N, and the winding taper is gradually reduced at a rate of 13%.
[0067] Comparative group: the polyolefin PP diaphragm: 100 parts of PP particle masterbatch.
[0068] The polyolefin PP diaphragm prepared by the present invention and the polyolefin PP diaphragm of the comparison group were tested by an online defect meter, and the results were as follows:
[0069] Online Defect Detector Number of crystal points (pcs / 1000m) <![CDATA[Crystal point area (mm 2 )]]> Embodiment 1 6 0.2-0.8 Embodiment 2 5 0.1-0.6 Embodiment 3 1 0-0.5 Comparison group 11 0.25-1.5
[0070] It has been verified that the present invention prepares a polyolefin PP diaphragm with the same thickness of 16um. The number of crystal points in the control group without adding antioxidants is significantly larger, and the area size ratio of the crystal points is different. By comparing the different antioxidant ratios, it can be seen that the improvement of the crystal points by the 1:1 ratio of the main antioxidant and the auxiliary antioxidant is more obvious.
[0071] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A polyolefin PP diaphragm with improved crystal point problem, characterized in that: The invention comprises the following components in parts by weight: 97-99 parts of PP particle masterbatch, 0.1-2 parts of main antioxidant and 0.1-2 parts of auxiliary antioxidant.
2. A polyolefin PP diaphragm for improving the crystal point problem according to claim 1, characterized in that: 98.5 parts of PP particle masterbatch, 0.75 parts of primary antioxidant, and 0.75 parts of auxiliary antioxidant.
3. The polyolefin PP diaphragm for improving the crystal point problem according to claim 1, characterized in that: The main antioxidant is a highly heat-resistant hindered ester or phenolic antioxidant, including but not limited to 1010 and 1098 types.
4. The polyolefin PP diaphragm for improving the crystal point problem according to claim 1, characterized in that: The auxiliary antioxidant is a fat-soluble antioxidant, including but not limited to 168 and 626 types.
5. The polyolefin PP diaphragm for improving the crystal point problem according to claim 1, characterized in that: The molecular weight of the PP particle masterbatch is 100,000-600,000.
6. A method for preparing a polyolefin PP diaphragm with improved crystal point problem, characterized in that: The following steps are involved: S1: Add the raw materials into the feeding kettle according to the following mass parts: 97-99 parts of PP particle masterbatch, 0.1-2 parts of primary antioxidant, and 0.1-2 parts of auxiliary antioxidant; S2: The feeding kettle stirs and mixes the added materials, and automatically feeds the materials to the extruder through a precise metering scale, and then melts and extrude them at high temperature in the extruder; S3: The high-temperature molten fluid is cast through a T-die and cooled by a casting roller; S4: Roll up the cast film and combine the four rolls of cast film into a large roll; S5: The cast film after the composite large roll is longitudinally stretched by a stretching machine, wherein the stretching equipment includes online heat treatment, heating stretching, heat setting, and winding; S6: The stretched and rolled film is peeled off with different layers by a layering machine and rolled into a semi-finished film; S7: The semi-finished film is passed through a slitting device and cut into a required width according to requirements to obtain a finished film.
7. The method for preparing a polyolefin PP diaphragm with improved crystal point problem according to claim 6, characterized in that: The mass ratio of the primary antioxidant to the auxiliary antioxidant in step S1 is 1:
1.
8. The method for preparing a polyolefin PP diaphragm with improved crystal point problem according to claim 6, characterized in that: In the step S1, the feeding kettle is weighed at a rate of ≥50 kg / h, with an accuracy of ≤±0.5%, a stirring speed of 100-300 rmp / s, and a stirring time of 2-4 min.
9. The method for preparing a polyolefin PP diaphragm with improved crystal point problem according to claim 6, characterized in that: In the step S2, the screw of the extruder is a single screw or a twin screw, the melt temperature of the extruder is 200-260°C, the film thickness is cooled to ≥100um in the step S3, and the temperature of the casting roller is 10-40°C.
10. The method for preparing a polyolefin PP diaphragm with improved crystal point problem according to claim 6, characterized in that: In step S5, the longitudinal stretching ratio is controlled to be 6-12 times, the longitudinal stretching speed is 5-20m / min, and in step S7, the slitting machine speed is controlled to be 80-200m / min, the unwinding tension is 20-50N, the winding tension is 5-20N, and the winding taper is gradually reduced at a ratio of 8%-20%.